FIGURATIVE LANGUAGE IN SONG LYRICS IN ED SHEERAN’S DIVIDE ALBUM - Yansyah, Heri; Arifin, M. Bahri; Setyowati, Ririn (Ilmu Budaya: Jurnal Bahasa, Sastra, Seni, dan Budaya, 2022)
Song lyrics have messages to convey to their listener and cannot be interpreted in literary ways. The researcher uses figurative language to analyze the song lyrics. This research is focused on the types of figurative language and its meaning used in Ed Sheeran’s Divide album. This research is included in descriptive qualitative research which is the appropriate method for analyzing the figurative language. There are two research questions in this research. The first research question is “what are the types of figurative language found in song lyrics in Ed Sheeran’s Divide album?”. The second research question is “what are the meanings of figurative language found in song lyrics in Ed Sheeran’s Divide album?”. By using Perrine’s theory, the result of the research showed that the types figurative language in song lyrics in Ed Sheeran’s Divide album are metaphor and metonymy. Beside metaphor and metonymy, the researcher also found another types of figurative language; such as simile, hyperbole, personification, understatement, and irony. By understanding the figurative language, the researcher is able to recognize the meaning of the song lyrics that contain figurative language. Most of the song lyrics in Ed Sheeran’s Divide album are about gratitude of the singer life and his finding in love. Based on the meaning that already found, the singer or the song writer mostly plays with associative meaning in order to use figurative language in his song lyrics.